The persistence of orientalism : Anglo-American historians and modern Egypt - Gran, Peter, 1941- (Middle East studies beyond dominant paradigms., 2020)
""The Persistence of Orientalism" is a study of Anglo-American historiography of modern Egypt, which emphasizes the work done by other professional historians, especially Edward Said"--